Sixty Years of Swedish Computational Lexicography - Dana Dannélls; Kristian Blensenius; Lars Borin (De Gruyter, 2025)
Swedish computational lexicography has a long history at the University of Gothenburg, both in its primary role as a central aspect of the scientific study of vocabulary and also as an infrastructural component for conducting research based on language data. Starting in the 1960s, the Språkdata research group pioneered corpus-supported lexicography for Swedish, forming the basis for successive editions of two main descriptive dictionaries of contemporary Swedish, SAOL and SO. Language technological lexical resources for Swedish have been developed by the research unit/research infrastructure Språkbanken Text since the turn of the millennium, most recently in the framework of the Swedish FrameNet++ initiative. After two decades of separation, these two largely mutually independently developed strands of computational lexicography have now joined forces under the umbrella of Språkbanken's lexical research infrastructure to advance the field technically, methodologically, and scientifically. The result is a vibrant and multifaceted research environment intertwined with and supported by a closely integrated cutting-edge computational infrastructure for working with lexical data